1993
DOI: 10.1128/mcb.13.6.3401
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional downregulation of the retina-specific QR1 gene by pp60v-src and identification of a novel v-src-responsive unit.

Abstract: The embryonic avian neuroretina (NR) is part of the central nervous system and is composed of various cell types: photoreceptors and neuronal and Muller (glial) inactivation. Cl is also a target for regulation during development. We have identified the DNA binding site for the Cl complex, a repeated GCTGAC sequence, and shown that mutations in this element abolish binding of this factor as well as transcription of the gene at the nonpermissive temperature. Neither formation of Cl nor that of C2 seems to invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…We showed that transcription of QR1 also correlates with cell quiescence in vitro, in NR cells expressing a v-src mutant, conditionally defective for its mitogenic capacity (Guermah et al, 1991). We identi®ed in the QR1 promoter a quiescence-responsive element, termed A box (Pierani et al, 1993, that displayed important similarities with the Maf recognition element (MARE) (Kataoka et al, 1994b). We also showed that transcription factors of the Maf family indeed regulate transcription of the QR1 gene through the A box .…”
Section: Introductionmentioning
confidence: 91%
“…We showed that transcription of QR1 also correlates with cell quiescence in vitro, in NR cells expressing a v-src mutant, conditionally defective for its mitogenic capacity (Guermah et al, 1991). We identi®ed in the QR1 promoter a quiescence-responsive element, termed A box (Pierani et al, 1993, that displayed important similarities with the Maf recognition element (MARE) (Kataoka et al, 1994b). We also showed that transcription factors of the Maf family indeed regulate transcription of the QR1 gene through the A box .…”
Section: Introductionmentioning
confidence: 91%
“…With the exception of studies on the QR1 gene (50,54), little is known regarding the mechanism by which v-Src down-regulates gene transcription. In this study, we used the ssecks gene as a prototype in order to explore the mechanisms involved in v-Src-mediated gene repression.…”
Section: Discussionmentioning
confidence: 99%
“…7345/+55; 71119/+55; 71173/+55; 71265/+55 and 71265A7/+55 reporter constructs have been described (Pierani et al, 1993). C7 mutation was introduced into 71173/+55; 71265/+55 and 71265A7/+55 plasmids by PCR mediated mutagenesis.…”
Section: Plasmid Constructionsmentioning
confidence: 99%
“…For each construct, one plate was subsequently incubated at 378C and the second at 418C. Forty hours later cell lysates were prepared and CAT and bgalactosidase activity measured as previously described (Pierani et al, 1993). Percentage of chloramphenicol conversion was calculated by scanning the thin layer chromatographic plates with a Phosphorimager instrument (Molecular Dynamics) and Image Quant Software.…”
Section: Transient Transfections and Cat Assaysmentioning
confidence: 99%
See 1 more Smart Citation